Analysis of the Online Identity of Public Figure Najwa Shihab: Analisis Identitas Daring Tokoh Public Najwa Shihab - Sejati, Tegas Immanio; Ramadhan, Rafly Aditya (Procedia of Social Sciences and Humanities, 2025)
Najwa Shihab has successfully built a strong and trustworthy online persona by prioritizing professionalism, ethics, and courage. Through a consistent approach and clear messaging, she effectively manages context collapse by utilizing content segmentation and low social media engagement. Despite facing challenges related to privacy and surveillance, Najwa uses her online platforms to inspire, educate, and mobilize society for positive change. This analysis examines how Najwa Shihab builds and maintains her online identity, manages interactions with diverse audiences, and addresses challenges related to reputation and privacy in the digital world. The findings show that while Najwa Shihab has successfully created a strong online presence, there is room to further develop strategies to protect her reputation and privacy. Highlights: Strategic Online Presence – Najwa Shihab maintains a trustworthy digital identity through professionalism, ethics, and clear messaging. Effective Context Management – She mitigates context collapse by segmenting content and keeping social media engagement minimal. Balancing Visibility & Privacy – While leveraging her platform for social impact, she faces challenges in reputation and privacy protection. Keywords: Najwa Shihab, Online Persona, Social Media, Professionalism, Ethics, Reputation, Privacy